Bankowość elektroniczna w Łąckim Banku Spółdzielczym - Klag, Łukasz (My University, 2014)
Autor pracy opisuje rozwój bankowość spółdzielczej w Polsce, a także bankowość elektroniczną w Łąckim Banku Spółdzielczym. Przeprowadza badania na temat postrzegania bankowości elektronicznej przez klientów banku.

The author describes the development of co-operative banking in Poland, as well as electronic banking at Lacki Cooperative Bank. The research has been conducted among bank customers on their perception of e-banking.
Electronic banking at Łącki Bank Spółdzielczy
Keywords: bank; bank społdzielczy; bank internetowy; sms bank; bankomat; karty płatnicze; bank; cooperative banks; internet banking; SMS banking; ATM; credit card